The ambiguity of transnational justice. The Inter-American case of human right - Arévalo Robles, Gabriel Andrés; Arévalo Robles, Luz Angela; Castellanos Cortés, Omaira Esperanza (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
Inter-American human rights justice is a phenomenon of transnational influence on the legal systems of national states. The growing interaction of the Inter-American Court with national judges and its work as interpreter of the American Convention on Human Rights (IACHR) has fostered excessive optimism that needs to be critically reviewed for the sake of a better understanding of transnational. To fulfill this task, this document will present the doctrinal discussions on justice, validity, and effectiveness of the IACHR through the scope, limits, and impact of the Inter-American judicial exercise.